Blended Learning (BL) as pedagogical alternative to teach business communication course: Case study of UUM Executive Diploma program - Dzakiria, Hisham (Anadolu University, 2012)
Globally, blended learning (BL) technologies have been increasingly applied in a variety of fields, both public and private sectors. In recent years, universities, public and private businesses and organizations are among those employing blended learning methods and technologies in training and re-training of professionals in the workforce. In Malaysia, the increasing use of blended learning to enhance learning and enriching of soft skills among professionals and individuals in the work place is evident.The advancement of technology is an onset to many new avenues and tool for learning and teaching, and it is the coalescing of these various technologies with particular pedagogy or and ragogy has helped to popularize BL.However, when an institution makes the critical choice of delivery methods, it is pertinent that the university needs to consider various success factors.One in particular is student - centered approach that entails the need to understand the students as the beneficiary of learning, and the support system they need to help them learn.This qualitative study reports in detail the experience of a small group of students undertaking Executive Diplomas at Executive Development Centre (EDC), Universiti Utara Malaysia as they progress through their Executive program. This paper looks at learning experiences as described by the learners-it is their story, their experience, and their perspective.This study suggests that BL offered a comfortable middle ground, and has lots of potential in higher education in Malaysia.It is a pedagogical alternative that could play a significant role not only for teaching Business Communication, but has the potential to promote lifelong learning initiatives in Malaysia in a much meaningful and inviting way.Although this study shows that BL contributed a significant and meaningful learning particularly for adult learners, it needs more definitive studies. Such information can be used to guide policy makers and educators as they plan national, regional,state, and local trainings and higher education programs for working professionals in Malaysia.